(untitled) (Contemporary Issues on Indonesian Human Rights Law and Policy, 2025)
This paper critically examines women’s land rights in Indonesia, focusing on how agrarian reform policies intersect with gender equality and human rights. Despite significant legal advancements in gender equity, women in rural and agrarian communities face persistent challenges in securing land ownership and control. Drawing on case studies from various provinces, the study explores the impact of Indonesia’s agrarian reform programs on women’s access to land and their ability to participate in decision-making processes related to land use. It analyzes the legal framework governing land rights, particularly the 1960 Basic Agrarian Law, and assesses its effectiveness in ensuring gender-inclusive land distribution. The paper also examines how social norms, patriarchy, and cultural practices impede women’s rights to own and control land. Using a human rights perspective, it emphasizes the need for reforms that address these structural barriers and promote gender justice in land governance. The research advocates for the integration of a gender-sensitive approach into Indonesia’s agrarian policies, highlighting the importance of land rights as a fundamental aspect of women’s economic empowerment and social justice. The paper concludes by proposing policy recommendations aimed at securing women’s land rights and ensuring their full participation in the nation’s agrarian reform agenda.